Morphometric and karyological study of Genista sericea (Cytiseae-Fabaceae) - Conti, Fabio; Bernardo, Liliana; Velari, Tiziana Cusma; Kosovel, Vera; Chiapella, Laura Feoli (Phytotaxa, 2014)
A morphometric and karyological study of several populations of Genista sericea, a northern Illyrian amphiadriatic species, with a disjunct distributional area centered on Pollino Massif (southern Italy), has been undertaken, based on herbarium specimens and field research. Morphometric analysis allowed to individuate three distinct groups of populations which are here attributed to three taxa at subspecific level. One of them is here newly described: G. sericea subsp. pollinensis, endemic to northern Calabria in Pollino and neighbouring areas of Basilicata. The taxonomic status of G. sericea var. rigida was re-evaluated and a name of a new rank is proposed: G. sericea subsp. rigida (occurring in southern Illyria), while subsp. sericea is a southeastern Alpine northern Illyrian taxon. The names G. sericea and G. sericea var. rigida are lectotypified. Karyologically, all the taxa are characterized by the same somatic number 2n = 48, sometimes with B chromosomes (up to four).